Fabrication of Antibacterial Poly(Vinyl Alcohol) Nanocomposite Films Containing Dendritic Polymer Functionalized Multi-Walled Carbon Nanotubes - Sapalidis, Andreas; Sideratou, Zili; Panagiotaki, Katerina N.; Sakellis, Elias; Kouvelos, Evangelos P.; Papageorgiou, Sergios; Katsaros, Fotios (Frontiers in Materials, 2018)
A series of Poly(vinyl alcohol) (PVA) nanocomposite films containing quaternized hyperbranched polyethyleneimine (PEI) functionalized multi-walled carbon nanotubes (ox-CNTs@QPEI) are prepared by solvent casting technique. The modified carbon based material exhibits high aqueous solubility, due to the hydrophilic character of the functionalized hyperbranched dendritic polymer. The quaternized PEI successfully wraps around nanotube walls, as polycations provide electrostatic repulsion. Various contents of ox-CNTs@QPEI ranging from 0.05 to 1.0 % w/w were employed to prepare functionalized PVA nanocomposites. The developed films exhibit adequate optical transparency, improved mechanical properties and extremely high antibacterial behavior due to the excellent dispersion of the functionalized carbon nanotubes into the PVA matrix.